2018
DOI: 10.31219/osf.io/x57fm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Callous unemotional traits, low cortisol reactivity and physical aggression in children: findings from the Wirral Child Health and Development Study

Abstract: Callous-unemotional (CU) traits are thought to confer risk for aggression via reduced amygdala responsivity to distress cues in others. Low cortisol reactivity is thought to confer risk for aggression via reduced arousal and this effect may be confined to boys. We tested the hypothesis that the association between childhood CU traits and aggression would be greatest in the absence of the inhibitory effects of cortisol reactivity, and that this effect would be sex dependent. Participants were 283 members of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The items at each age were allowed to vary to reflect developmental differences in the manifestation of CU traits and measurement invariance by sex was established for the measure at each age point. We have provided evidence for the validity of the age 5.0 CU traits measure in Wright et al (2019) by demonstrating incremental prediction to physical aggression at age 7.0, controlling for age 5.0 aggression. For this analysis, a latent variable was created from the factor scores from the three age time points to represent CU traits from 2.5 to 5.0 years.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The items at each age were allowed to vary to reflect developmental differences in the manifestation of CU traits and measurement invariance by sex was established for the measure at each age point. We have provided evidence for the validity of the age 5.0 CU traits measure in Wright et al (2019) by demonstrating incremental prediction to physical aggression at age 7.0, controlling for age 5.0 aggression. For this analysis, a latent variable was created from the factor scores from the three age time points to represent CU traits from 2.5 to 5.0 years.…”
Section: Methodsmentioning
confidence: 79%
“…The study used a two stage stratified design in which a consecutive general population sample (the ‘extensive’ sample) is used to generate a smaller ‘intensive’ sample stratified by psychosocial risk with more detailed measurement over time, and both are followed in tandem. The sample stratification has been described previously (Sharp et al, 2012; Wright et al, 2019) but in brief, the stratification was based on maternal responses to questions about psychological abuse in their current or recent partner relationship (Moffit et al, 1997). The stratification variable was chosen for its known association with a variety of risk factors for early child development.…”
Section: Methodsmentioning
confidence: 99%
“…The anterior insula, which is involved in the salience network, is associated with social cognition and evaluation, and is sensitive to social saliency (Achterberg et al, 2016; Achterberg et al, 2018; Cacioppo et al, 2013). In addition, prior studies found that 19% of the variance in callous‐unemotional traits was explained by the GMV of the anterior insula in males, and callous‐unemotional traits were related to physical aggression (Raschle et al, 2018; Wright, Hill, Pickles, & Sharp, 2019). The fMRI studies also showed an association between anterior insula and reactive aggression and motor impulsivity (Chester et al, 2014; Dambacher et al, 2015; Werhahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the effect of CU traits on later aggression may be attenuated in the presence of alternative sources of restraint. These may be internal, for example, higher levels of physiological arousal [2] or increased mentalisation [3]. External restraint in the presence of elevated CU traits may also be provided by positive reinforcement for prosocial behaviours, or by warm supportive parenting which may promote the internalisation of social norms and prosocial behaviour [4,5].…”
Section: Introductionmentioning
confidence: 99%